The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2201.11551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Super-Alfvénic Rotational Instability in accretion disks about black holes

Hans Goedbloed,
Rony Keppens

Abstract: The theory of instability of accretion disks about black holes, neutron stars or protoplanets, is revisited by means of the recent method of the Spectral Web. The cylindrical accretion disk differential equation is shown to be governed by the forward and backward Doppler-shifted continuous Alfvén spectra Ω ± A ≡ mΩ ± ω A , where ω A is the static Alfvén frequency. It is crucial to take non-axisymmetry (m = 0) and super-Alfvénic rotation of the Doppler frames (|mΩ|A and Ω − A then overlap, ejecting a plethora o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Localized nonaxisymmetric MRI mode structures were found to be confined between the Alfvénic resonant points (where the magnitude of the Doppler-shifted wave frequency is equal to Alfvén frequency (Matsumoto & Tajima 1995). In cylindrical shear flows (Ogilvie & Pringle 1996) and in the compressible limit (Goedbloed & Keppens 2022), it was shown that forward and backward overlapping of these Alfvén continua results in discrete localized nonaxisymmetric modes at large axial and azimuthal mode numbers. The question arises whether in a real domain with spatial curvature, global non-axisymmetric modes with real frequencies can persist.…”
Section: Introductionmentioning
confidence: 97%
“…Localized nonaxisymmetric MRI mode structures were found to be confined between the Alfvénic resonant points (where the magnitude of the Doppler-shifted wave frequency is equal to Alfvén frequency (Matsumoto & Tajima 1995). In cylindrical shear flows (Ogilvie & Pringle 1996) and in the compressible limit (Goedbloed & Keppens 2022), it was shown that forward and backward overlapping of these Alfvén continua results in discrete localized nonaxisymmetric modes at large axial and azimuthal mode numbers. The question arises whether in a real domain with spatial curvature, global non-axisymmetric modes with real frequencies can persist.…”
Section: Introductionmentioning
confidence: 97%